HLA-DQ2 and HLA-DQ8 Haplotypes Influences Circulating Levels of Anti-Tissue Transglutaminase and Anti-Gliadin Antibodies in Celiac Disease - Ban Waheed Hussein Bdair; Satar Jabbar Rahi Algraittee (American Journal of Biology and Natural Sciences, 2025)
Celiac disease indicates symptoms like damage to small intestinal mucosa, and challenges with nutrient absorption when gluten is consumed by individuals who are genetically predisposed. Genetic, immunological, and environmental factors play important roles in the pathogenesis of the diseases. Here, we briefly reviewed how specific haplotypes linked with genetic risk of celiac disease influence the levels of serological markers associated with the disease. By understanding this link, personalised medicine methods based on genetic risk could be created, thereby potentially improving early disease diagnosis, accuracy of diagnosis, patient care and treatment methods.